Isolated Rectal Perforation Presenting as Peritonitis in a Child with Enteric Fever - Chaubey, Digamber; Verma, Ajay Kumar; Pandey, Anand; Gupta, Archika (Journal of Child Science, 2017)
Typhoid fever is common in developing countries. It may lead to bowel perforation. Terminal ileum is the most frequent site of perforation. However, perforation at uncommon sites such as rectosigmoid junction may occur occasionally. In this study we report a patient who we treated for perforation peritonitis; on exploratory laparotomy, it turned out to be a rectal perforation. The patient was operated successfully. As an unusual presentation, it is being reported with a review of the relevant literature.
Keywords: typhoid; perforation; fever; rectal perforation